EFFECT OF AUTHORITATIVE PARENTING STYLES ON ACADEMIC PERFORMANCE IN THE SCIENCES AMONG HIGH SCHOOL STUDENTS IN KABALE DISTRICT. A CROSS-SECTIONAL STUDY. - Muhwezi, Murari Maurice Alex; Kiyingi, Frank Pio (Student’s Journal of Health Research Africa, 2024)
Background Authoritative parenting, as a parenting style, has garnered significant attention and study in the field of psychology, particularly about its impact on self-esteem and academic performance. The study aims to assess the effect of authoritative parenting styles on academic performance in the sciences among high school students in the Kabale district. Methodology A cross-sectional design in which a sample of 201 respondents was that consisted of both male and female students from the selected secondary schools. A simple random sampling technique was employed in both the selection of schools and participants. The study applied Pearson product-moment correlation to examine the relationship among the variables. Results The prevalence of authoritative parenting style among the respondents, with a grand mean of 3.99 indicates that a majority of participants agreed that their parents practice. A significant number of respondents stated agreement (M = 4.29, SD = 1.03) that their parents are responsive to their feelings and needs. Respondents’ agreement (M = 4.30, SD = 0.97) that their parents explain their feelings about their good or bad behavior reflects open communication. The respondents’ agreement (M = 4.02, SD = 1.18) that parents explain expectations (M = 3.97, SD = 1.16). Findings highlight that parents’ consideration of children’s preferences in family plans (M = 3.72, SD = 1.24) and treating them as equal family members (M = 4.53, SD = 0.81) reinforce authoritative parenting’s focus on respect for individuality and fostering a sense of belonging. There was no statistically significant relationship between authoritative parenting style and academic performance in sciences, given r (199) = -.002, ρ = .490. Conclusion There was no statistically significant relationship between authoritative parenting style and academic performance in the sciences. Recommendations Parents should strive to adopt a balanced parenting style that blends authority with open communication.